Cane molasses and hemicelluloses extract (wood molasses) in rations for finishing steers. The value of shelter for finishing cattle - Pfost, H.B.; Smith, E.F.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
the only variable planned in the diet was type of molasses, which composed 16% of the self-fed roughage-concentrate mixture. Cane molasses was used in two lots; hemicelluloses extract in two lots. The self-fed roughage-concentrate mixture was composed of these ingredients: soybean oil meal, 10%; rolled sorghum grain, 40%; ground rice hulls, 35%; molasses, 10%l urea, dicalcium phosphate and premix, 1% each. The premix supplied 10 mgs. Stillbesterol, 70 mgs. Aureomycin and 28,000 I.U. Vitamin A per steer daily.
Keywords: Beef; Cane molasses; Hemicelluloses extract; Finishing steers